Ex vivo magnetic particle imaging of vascular inflammation in abdominal aortic aneurysm in a murine model - Mangarova, Dilyana B.; Brangsch, Julia; Mohtashamdolatshahi, Azadeh; Kosch, Olaf; Paysen, Hendrik; Wiekhorst, Frank; Klopfleisch, Robert; Buchholz, Rebecca; Karst, Uwe; Taupitz, Matthias; Schnorr, Joerg; Hamm, Bernd; et al. (Scientific Reports, 2020)
Abdominal aortic aneurysms (AAAs) are currently one of the leading causes of death in developed countries. Inflammation is crucial in the disease progression, having a substantial impact on various determinants in AAAs development. Magnetic particle imaging (MPI) is an innovative imaging modality, enabling the highly sensitive detection of magnetic nanoparticles (MNPs), suitable as surrogate marker for molecular targeting of vascular inflammation. For this study, Apolipoprotein E-deficient-mice underwent surgical implantation of osmotic minipumps with constant Angiotensin II infusion. After 3 and 4 weeks respectively, in-vivo-magnetic resonance imaging (MRI), ex-vivo-MPI and ex-vivo-magnetic particle spectroscopy (MPS) were performed. The results were validated by histological analysis, immunohistology and laser ablation-inductively coupled plasma-mass spectrometry. MR-angiography enabled the visualization of aneurysmal development and dilatation in the experimental group. A close correlation (R = 0.87) with histological area assessment was measured. Ex-vivo-MPS revealed abundant iron deposits in AAA samples and ex-vivo histopathology measurements were in good agreement (R = 0.76). Ex-vivo-MPI and MPS results correlated greatly (R = 0.99). CD68-immunohistology stain and Perls’-Prussian-Blue-stain confirmed the colocalization of macrophages and MNPs. This study demonstrates the feasibility of ex-vivo-MPI for detecting inflammation in AAA. The quantitative ability for mapping MNPs establishes MPI as a promising tool for monitoring inflammatory progression in AAA in an experimental setting.
CRIS-Team Scopus Importer:2023-03-08